Implementation of the Talqin Method Using Audio Media to Optimize Qur’anic Reading Skills in Elementary Students at SD IT Insan Madani - Yunisa, Yunisa; Nur Sejahtera, Nur Sejahtera; Setiawan, Hasrian Rudi; Afandi, Mursid (Yayasan Rahmat Islamiyah, 2025)
This study aims to examine the implementation of the Talqin method assisted by audio media in optimizing Qur’anic reading skills among elementary students at SD IT Insan Madani. The Talqin method is a learning approach that emphasizes repetition and imitation of correct pronunciation, which is considered effective in developing proper Qur’anic reading abilities. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The findings show that the use of the Talqin method with audio media significantly improves students' tajweed proficiency and reading fluency. Moreover, audio media enables students to learn independently outside regular class hours. Therefore, integrating the Talqin method with audio technology is an effective strategy to enhance Qur’anic literacy at the elementary level.